Sphingolipid metabolism in T cell responses after allogeneic hematopoietic cell transplantation - Tian, Linlu; Ogretmen, Besim; Chung, Brian Y.; Yu, Xue-Zhong (Frontiers in Immunology, 2022)
Allogeneic hematopoietic cell transplantation (allo-HCT) is an effective immunotherapy against hematopoietic malignancies. The infused donor lymphocytes attack malignant cells and normal tissues, termed a graft-verse-leukemia (GVL) effect and graft-verse-host (GVH) response or disease (GVHD), respectively. Although engineering techniques toward donor graft selection have made HCT more specific and effective, primary tumor relapse and GVHD are still major concerns post allo-HCT. High-dose systemic steroids remain to be the first line of GVHD treatment, which may lead to steroid-refractory GVHD with a dismal outcome. Therefore, identifying novel therapeutic strategies that prevent GVHD while preserving GVL activity is highly warranted. Sphingolipid metabolism and metabolites play pivotal roles in regulating T-cell homeostasis and biological functions. In this review, we summarized the recent research progress in this evolving field of sphingolipids with a focus on alloreactive T-cell responses in the context of allo-HCT. We discussed how sphingolipid metabolism regulates T-cell mediated GVH and GVL responses in allo-HCT and presented the rationale and means to target sphingolipid metabolism for the control of GVHD and leukemia relapse.